Let's solve for \( p \) step by step. You already set up the equation correctly.
Starting with the equation you provided:
\[ 20 - 2p = 6 + 5p + 2p + 2p \]
First, simplify the right side of the equation:
\[ 20 - 2p = 6 + (5p + 2p + 2p) \] \[ 20 - 2p = 6 + 9p \]
Now, isolate the \( p \) terms by moving \( 9p \) to the left side and \( 2p \) to the right side:
\[ 20 - 6 = 9p + 2p \] \[ 14 = 11p \]
Next, divide both sides by 11 to solve for \( p \):
\[ p = \frac{14}{11} \]
So, the value of \( p \) is \( \frac{14}{11} \) or approximately \( 1.27 \).